STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN GURU - Widya Intan Sari; Aliman Aliman; Puspa Djuwita (Manajer Pendididikan, 2017)
The purpose of this study was to describe the strategic management conducted principals in improving the discipline of teachers in number one senior high shool of Kepahiang. This research uses descriptive study with a qualitative approach. The data collection techniques by interview, observation and documentation. Subjects were principals, vice principals affairs curriculum, teachers, school supervisors supervisor and chairman of the school committee. While the data analysis was done with descriptive analysis, inductive and deductive. Strategy formulation principals in enforcing discipline the teacher is the formulation of the vision and mission by considering the internal and external environment, followed by setting goals and targets and the continued determination of the strategy. Implementation of the strategy principals in enforcing discipline the teacher is doing the translation strategies have been formulated in the form of activities. Evaluation is done by supervising the education of the teachers.